Effect of Isomerization on the Reversible Reaction of Hydrogenation‐Dehydrogenation of ortho‐Terphenyl on a Pt/C Catalyst. Issue 9 (1st August 2018) - Kalenchuk, Alexander N.; Bogdan, Victor I.; Dunaev, Sergei; Kustov, Leonid M.
Abstract: Reversible catalytic hydrogenation‐dehydrogenation reactions of ortho ‐terphenyl ( o ‐terphenyl) as one of the most promising materials for hydrogen storage were investigated. The conversion of o ‐terphenyl is 100 % and the selectivity to perhydro‐ o ‐terphenyl reaches 99 % in the first cycle of hydrogenation on a commercial Pt/C catalyst. The dehydrogenation process in a flow reactor is accompanied by the formation of isomerization products of o ‐terphenyl, in particular, exhaustively and partially hydrogenated compounds formed from meta ‐terphenyl ( m ‐terphenyl) and triphenylene. These substrates are subject to hydrogenation independently during the second hydrogenation cycle, which reduces the selectivity of recyclization of o ‐terphenyl. Dodecahydrotriphenylene demonstrates a higher reactivity during the second cycle of dehydrogenation compared to perhydro‐ o ‐terphenyl. The amount of generated hydrogen is consistent with the kinetic data. Abstract : The role of isomerization processes in hydrogen storage based on aromatic substrates is evaluated. In particular, the effect of isomerization on the reversible reaction of hydrogenation‐dehydrogenation was analyzed using one of the most efficient substrates, o ‐terphenyl, with a commercial Pt/C catalyst applied successfully in both hydrogenation and dehydrogenation processes.